Cognitive Stimulation Therapy (Indonesian Version): Effects on Factors Associated with Cognitive Function in Middle Adult - Aniek Puspitosari; Ninik Nurhidayah (Postgraduate, University of Mataram, 2025)
Cognitive development in adulthood involves the ability to better integrate emotion and logic to make decisions and a reduced ability to process information quickly. In late adulthood, cognitive development is characterized by neurocognitive disorders, intellectual changes, and memory changes. When cognitive decline is regarded as a continuous process from normal cognitive function to mild cognitive impairment and dementia, the identification and management of influential factors such as cognitive decline-related demographic characteristics, comorbid diseases and health habits may contribute to the delay or prevention of dementia. Cognitive Stimulation Therapy (CST) is an intervention that aims to stimulate the cognitive function of middle adult individuals aged 50-60 years with cognitive activities. This study aims to determine the effect of Cognitive Stimulation Therapy on factors of cognitive function of middle adult individuals aged 50-60 years in Kemiri Village, Kebakkramat District, Karanganyar Regency. This research is a quantitative-research with a pre-experimental design with one group pre-post test. The sampling technique used was purposive sampling with a sample size of twenty-seven people. The instrument used was the Indonesian Version of the Montreal Cognitive Assessment (MoCA-Ina). Cognitive Stimulation Therapy (CST) was carried out in 6 sessions over 8 weeks. Data analysis using paired t-test (paired t-test). Paired t-test results Sig. (2-tailed) = 0.000, which means p-value < 0.05, which shows that Cognitive Stimulation Therapy has an effect on the cognitive abilities of middle adult individuals aged 50-60 years in Kemiri Village, Kebakkramat District, Karanganyar Regency.